THE EFFECT STUDENT’S VIEW OF PARENTS PATTERN AND CRITICAL THINKING STUDENT TO ENGLISH LEARNING ACHIEVMENT - Nurulia Falah; Julinda Siregar (INFERENCE: Journal of English Language Teaching, 2019)
This study aims to determine the effect of parenting, critical thinking skills, and English learning achievement together. The research method used was a survey, with a total sample of 60 people in Junior High School. Data collection uses a questionnaire. Data analysis carried out gave results: 1) Parenting and critical thinking skills together positively and significantly influenced English learning achievement. The formed regression equation is  = 31,689 + 0,252X1 + 0,244X2; with a regression significance of Sig. 0,000 < 0.05 and Fh = 9,049. 2) Parenting pattern has a positive and significant influence on English learning achievement; this is shown by the value of Sig 0,026 < 0,05 dan the = 2,285. 3) Critical thinking has a positive and significant influence on English learning achievement. This is shown from the value of Sig 0,035 < 0,05 dan the = 2,166. Keywords: parenting pattern: critical thinking: English: study.